Financing food systems in times of global disorder - Swinnen, Johan (Springer, 2025)
Global development financing is transforming alongside trade and political disruptions. We should focus on creating a more diverse and efficient food finance system, including repurposing public support and leveraging private investments, says Johan Swinnen. For full text of article see https://rdcu.be/eFev2